CLINICAL USEFULNESS OF CELL SAVER FOR REDUCTION OF THE BLOOD TRANSFUSION VOLUME IN OPEN HEART SURGERY - KATO, M.; ONISHI, K.; YOSHII, Y.; OHKUBO, N.; HIRAMATSU, M.; TAKANO, H.; YASUDA, H. (Jinko Zoki, 1990)
To determine whether the CELL SAVER (CS) could reduce blood transfusion volume in the open heart surgery, multiple regression analysis for the transfusion volume and discriminant analysis for non-blood transfusion surgery, were performed using perioperative 21 factors including a factor of CS use in 106 patients open heart surgery. Both analysis revealed that CS use remained significant factor for transfusion volume reduction or non-blood transfusion surgery even after reduction of 21 to 6 factors in multiple regression analysis and 21 to 4 factors in discriminant analysis, in addition to the fact that the transfusion volume reduced 3288 to 1473ml by the introduction of CS and that the incidence of resultant serum hepatitis reduced 25.9 to 12.5%. Thus these results suggest that CS might be of clinical use in terms of reduction of transfusion blood volume in open heart surgery and the incidence of resultant hepatitis.